China's outward direct investment and its impact on the domestic economy - Molnar, Margit (OECD Economics Department Working Papers, 2021)
Overseas direct investment by Chinese firms increased eight fold over the past decade, making the country as an important investor in stock terms as Japan. Investing in leasing and business services appears to make up nearly half of China's ODI stock according to official sources, though it is over-estimated owing to the fact that all investment through third parties and vehicles appears under this sector, not under the one where the investment is actually made. Correcting for this caveat by using firm-level M&A and greenfield investment data indicates that in fact China's ODI mostly goes to resource-based manufacturing. Also, China is just as an important manufacturing investor as is Japan. Estimation results show that overseas direct investment affects domestic employment negatively in the majority of sectors, indicating substitution instead of a complementary relationship. Furthermore, ODI reduces the speed of labour market adjustment to its long-run equilibrium and increases the domestic price elasticity of demand for labour. There is considerable heterogeneity across sectors, but the impact of ODI on domestic fixed asset investment tends to be negative in most sectors